'Les dialectes montagnards' [The mountain dialects]: towards redefining the Berber status and language attitudes in post-Arab Spring Tunisia. Issue 1 (2nd January 2022) - Gabsi, Zouhir
ABSTRACT: ' Les dialectes montagnards' is the name given by local authorities in the pre-Arab spring period to those languages that are falsely classified as Arabic dialects. What they refer to in reality is the Berber language(s). The Arab Spring has had an observable impact on Tunisia in most fields of enquiry, except for the place of the Berber language in the Arab Spring narrative. The present government, like its predecessor, fails to recognise the Berber language in its language policy and planning. The new-found freedom of expression and association failed to serve as a catalyst for the Berbers to seek recognition and demand institutional support to maintain their language and their cultural heritage. This paper surveys the Berber speakers of Douiret (Southern Tunisia) and seeks to examine their attitude and aspirations to maintaining Berber in the post-Arab Spring context. The research shows that almost interviewees, regardless of gender, age, and education, have expressed a strong desire to maintain Berber, mainly through education to improve its socio-political status. The paper also demonstrates that despite the signs of Berber 'awakening' mirrored in their demands for recognition, both locally and internationally, socio-economic and political grievances play a role in the marginalisation and attrition of the Berber language. Based on several fieldwork visits to the region since 2003, the paper reflects on the role of the researcher as a humanist in advocating the maintenance of a language, while acknowledging that its speakers' priorities may take different trajectories on the map of the human condition.